LAND AS A KEY ELEMENT OF RESOURCE POTENTIAL OF AGRICULTURAL ENTERPRISES OF TERRITORIAL COMMUNITIES OF IVANO-FRANKIVSK REGION - Drabchuk, N.Yu. (The actual problems of regional economy development, 2021)
The article is aimed at researching the issues related to land as a key element of the resource potential of agricultural enterprises of territorial communities of Ivano-Frankivsk province. The objective of the article is to study the resource potential of agricultural enterprises, namely land as its key element, particularly, for the territorial communities of Ivano-Frankivsk region. To achieve this goal, the article used the following research methods: dialectical method of cognition - in the study of scientific sources on the interpretation of the concept of “resource potential”, graphic - to reflect the structural model of resource potential of agricultural enterprises, grouping and analysis of research, abstract-logical - for generalization of theoretical positions, formation of conclusions and offers. The article different approaches of scientists to the interpretation of the category "resource potential", substantiates the structure of resource potential of agricultural enterprises, examines the specifics of agricultural enterprises in the territorial communities of Ivano-Frankivsk region, depending on the availability of the necessary elements of resource potential for the production capacity of these enterprises; it is established that in modern economic conditions, land resources can become an important resource for community development, the use of which will allow, on the one hand, to increase local budget revenues in the form of land fees and taxes, and on the other hand, expand the infrastructure base and develop management mechanisms in the field of terrestrial relations. The scientific novelty of the study is the grouping and analysis of agricultural enterprises and land area in their use, according to their location, affiliation, and quantity, in relation to the relevant territorial community of Ivano-Frankivsk region, as well as in the graphical representation of the area of land of agricultural enterprises in the structure of the area of districts. The results obtained during the study can be mutually used by agricultural enterprises and local communities to develop their joint work to improve resource potential within land-dwelling relations.